Designing a Low-Cost Multifunctional Infant Incubator. (June 2014) - Tran, Kevin; Gibson, Aaron; Wong, Don; Tilahun, Dagmawi; Selock, Nicholas; Good, Theresa; Ram, Geetha; Tolosa, Leah; Tolosa, Michael; Kostov, Yordan; Woo, Hyung Chul; Frizzell, Michael; et al.
Every year, an unacceptably large number of infant deaths occur in developing nations, with premature birth and asphyxia being two of the leading causes. A well-regulated thermal environment is critical for neonatal survival. Advanced incubators currently exist, but they are far too expensive to meet the needs of developing nations. We are developing a thermodynamically advanced low-cost incubator suitable for operation in a low-resource environment. Our design features three innovations: (1) a disposable baby chamber to reduce infant mortality due to nosocomial infections, (2) a passive cooling mechanism using low-cost heat pipes and evaporative cooling from locally found clay pots, and (3) insulated panels and a thermal bank consisting of water that effectively preserve and store heat. We developed a prototype incubator and visited and presented our design to our partnership hospital site in Mysore, India. After obtaining feedback, we have determined realistic, nontrivial design requirements and constraints in order to develop a new prototype incubator for clinical trials in hospitals in India.